The Effect of Tax Knowledge and Tax Socialization on Tax Planning with Tax Reporting as a Moderating Variable: English - Hariadi, Sugeng; Febrianti, Rindang (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
This research is about the Effect of Tax Knowledge and Tax Socialization on Tax Planning with Tax Reporting as a Moderating Variable. The dependent variable in this study is Tax Planning. The independent variables in this study are Tax Knowledge and Tax Socialization. The Moderating Variable in the study is Tax Reporting. This research was conducted at a coffee shop located in the Sudimoro Region, Malang City, East Java. The number of respondents in this study were 50 respondents. The sampling method used is the Questionnaire and Interview method. The results of this study conclude that tax knowledge has a significant positive effect on tax planning, tax socialization has a significant positive effect on tax planning. For the interaction of moderation of tax reporting concluded that the results were able to moderate tax knowledge of tax planning and for the interaction of moderation of tax reporting concluded that the results were able to moderate tax socialization of tax planning.